Structural changes in the duration of bull markets and business cycle dynamics - Nicolau, João (2018)
This paper tests for structural changes in the duration of bull regimes of adjusted market capitalization stock indexes comprehending 18 developed and emerging economies, using a novel approach introduced by Nicolau (2016); and investigates whether the structural changes detected in the bull markets' duration are connected to the business cycle. Interestingly, the results show that structural changes in the duration of bull market regimes seem to anticipate periods of economic recession. The results provide statistically significant evidence that decreases in bull markets duration do not occur independently from economic crises, as 13 out of the 18 markets considered in our sample verify such decreases at least 12 months prior to the occurrence of an economic crisis. Additionally, these structural changes seem to affect smaller companies first, and then the larger ones. The association between decreases in the bull market regimes' duration and economic crises is possibly a consequence of the financial markets' leading behavior over the economy, with these structural changes serving as proxies for decreasing confidence in the financial markets, which naturally affects economic stability.